The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ijscr.2017.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal adenocarcinoma five years after laparoscopic sleeve gastrectomy. A case report

Abstract: HighlightsThere is big concern about reflux appearance after sleeve gastrectomy.Chronic reflux increases risk of esophageal adenocarcinoma.We present a case of an esophageal adenocarcinoma after sleeve gastrectomy.Relationship between sleeve gastrectomy and reflux needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 16 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…Another case reported by Sohn [ 9 ] described esophageal adenocarcinoma 2.5 years after SG also without previous endoscopic evaluation. In a recent publication, Wright [ 10 ] described esophageal adenocarcinoma five years after SG in a patient with normal previous preoperative gastroscopy. Our case is the only one with BE without dysplasia detected before SG.…”
Section: Discussionmentioning
confidence: 99%
“…Another case reported by Sohn [ 9 ] described esophageal adenocarcinoma 2.5 years after SG also without previous endoscopic evaluation. In a recent publication, Wright [ 10 ] described esophageal adenocarcinoma five years after SG in a patient with normal previous preoperative gastroscopy. Our case is the only one with BE without dysplasia detected before SG.…”
Section: Discussionmentioning
confidence: 99%
“…One should add that Barrett's metaplasia can be found in only 1.6% of the average population [21]. Esophageal adenocarcinoma after SG has been reported in a small number of cases [22,23]. For instance, El Khoury et al published a case report of esophageal adenocarcinoma in BE found even 3 years after SG [24].…”
Section: Barrett's Esophagus After Sleeve Gastrectomymentioning
confidence: 99%
“…Several reports have stated an increased risk of Barrett's esophagus and increased GERD after SG [13,14]. To our knowledge 3 cases of esophageal adenocarcinoma have been reported after SG [15]. According to the International Sleeve Gastrectomy Expert Panel Consensus Statement severe esophagitis and Barrett's esophagus are contraindications for SG.…”
Section: Discussionmentioning
confidence: 97%